2007
DOI: 10.1590/s0101-60832007000300004
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento do transtorno de ansiedade social em crianças e adolescentes

Abstract: ResumoContexto: Transtorno de ansiedade social é um transtorno incapacitante e altamente prevalente em crianças e adolescentes ao longo da vida, de acordo com os critérios do DSM-IV, variando de 0,7% a 3,5%. Se não tratado, pode interferir no funcionamento emocional, social e escolar. Objetivos: Avaliar a evidência atual para a eficácia e efetividade de intervenções farmacológicas e psicoterápicas no tratamento do transtorno de ansiedade social na infância e na adolescência. Métodos: Pesquisas foram realizadas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
13

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 30 publications
0
2
0
13
Order By: Relevance
“…It is considered that the mental health problems in university students may also favor problems in social functioning, emotional and school problems (Isolan et al, 2007), and increased stress (Fernandes & Land, 2008), which, in a certain way, restricts the possibilities for development in this crucial time for the adult, professional, and personal roles. It was verified that the literature is inconclusive regarding the relationship between anxiety and social skills, with some authors having reported such a relationship (Angélico et al, 2006) and others not (Levitan et al, 2008), which is the insertion context of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is considered that the mental health problems in university students may also favor problems in social functioning, emotional and school problems (Isolan et al, 2007), and increased stress (Fernandes & Land, 2008), which, in a certain way, restricts the possibilities for development in this crucial time for the adult, professional, and personal roles. It was verified that the literature is inconclusive regarding the relationship between anxiety and social skills, with some authors having reported such a relationship (Angélico et al, 2006) and others not (Levitan et al, 2008), which is the insertion context of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The study of social anxiety and of the possible predictor variables of this condition has an important potential contribution due to the high comorbidity of anxiety with other disorders (Dozois & Westra, 2004), the presence of impairments in emotional, social and school functioning (Isolan, Pheula, & Manfro, 2007), and its associations with stress (Fernandes & Terra, 2008). Additionally, as stated by Iancu and Goldstein (2009) in relation to social anxiety, there is a vicious circle, because social isolation in general reduces social interactions, which in turn, increases deficits in the appropriate social skills, increasing social anxiety and feelings of inferiority.…”
mentioning
confidence: 99%
“…Dados epidemiológicos sugerem que os TA tenham maior prevalência entre adolescentes do que em crianças e indivíduos adultos. Estes inquéritos ainda afirmam que os casos que se iniciam na adolescência têm maior risco de se estender até a idade adulta, e raramente apresentam remissão (7)(8) .…”
Section: Discussionunclassified
“…Os dados encontrados neste estudo corroboram com os registros apontados por outros estudos (7)(8) , ou seja, os TA foram mais prevalentes entre adolescentes (299-26,6%). Pesquisadores (6,9) ressaltam que na maioria dos casos o desenvolvimento de TA pelos jovens está associado aos instintos naturais de um ser em fase peculiar de desenvolvimento, com a vontade de se tornar independente, a opressão social ou econômica, ou até mesmo por perturbações hormonais.…”
Section: Discussionunclassified
“…No entanto, em alguns casos, até crianças de sete ou oito anos são afetados, infelizmente com um prognóstico menos que esperançoso. (14) O conhecimento do profissionais a respeito dos transtornos de fobia social certamente influenciará a terapia do paciente, uma vez que é provável que a doença imponha algumas restrições sobre o estilo de vida deste. Portanto, baseado nessas considerações, ao comparar o perfil do fóbico social ao dos sujeitoscontrole, surgem como pessoas economicamente desfavorecidas com baixo nível de educação, solteiras, dependentes de outros e afetadas por outros transtornos mentais, com dificuldade de manter um emprego, baixo desempenho no trabalho e isolação social causada por habilidades sociais inaceitáveis, apoio social deficiente e ideação suicida.…”
Section: Fobia Social: Discussão Das Evidênciasunclassified